Pengaruh Pembelajaran Reflektif dan Metakognisi terhadap Penalaran Klinik Mahasiswa Program Profesi Dokter - Eti Poncorini Pamungkasari; Amitya Kumara; Armis Armis; Ova Emilia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2015)
Background: Most clinical students still have difficulties in clinical reasoning process. Previous study mentioned that reflection and metacognition are factors could influence clinical reasoning. This study aimed to measure the effect of reflection, metacognition, age, sex, duration of clinical rotation, duration of undergraduate program taken by students, and students’ final remark on undergraduate program to students’ clinical reasoning.Method: This study was a quasi-experimental pretest postest control group design, conducted at RSUD Dr Moewardi Surakarta. We selected 185 clinical students by purposive sampling technique. The study used the Metacognitive Awareness Inventory (‘the MAI’), Motivation scale on Motivated Strategies for Learning Questionnaire (‘the MSLQ’), and Script Concordance Test as instruments. The analyses used multiple linier regressions. Results: The intervention of reflection learning increased clinical reasoning 1,11 unit (p=0,319); The increase of 1 unit score metacognition decreased clinical reasoning 0,01 score (p=0,806), increasing one semester duration of undergraduate program decreased clinical reasoning 1,17 score (p=0,297), increasing students’ final remark on undergraduate program increased clinical reasoning 15,98 score (p=0,006), female students had 1,97 lower score of clinical reasoning than male (p=0,103), increasing one month of duration clinical rotation increased clinical reasoning 0,01 score (p=0,958), increasing one score of motivation increased clinical reasoning 0,01 score (p=0,529). Conclusion: Clinical learning and metacognition can not influence clinical reasoning significantly. Clinical teacher and clinical students should be familiarized with reflection learning. Further researches are needed to exploring influencing factors to clinical reasoning.